On the derivation of local/regional geodetic system - STOYANOV, Lyubomir; IVANOV, Roumen A. (Contributions to Geophysics and Geodesy, 2021)
The systemic and technological aspects in derivation of the national/regional integrated geodetic system are set out. Here, instead of consistency of three independently derived reference systems, the procedures are suggested which integrate networks, technologies, data and models connecting elements from different reference systems. The proposed procedures should be applied to the following areas 1) the design of layers of the complex basic geodetic network, 2) the measurement technologies in building of network, 3) the consistency of datums, 4) the modelling of inhomogeneous data, 5) the comparison and concordance of results, obtained by different methods. In order to analyse these procedures a term “integrating process” is introduced. The different elements, stages and varieties of these processes are set out. Two technological schemes for determination of the consistent parameters of geodetic system by means of integrating processes are proposed. The procedures for derivation of an integrated system with corresponding to it geocentric 4D integrating geodetic datum are outlined. It is suggested the materialization of the system to be realized by integral basic geodetic network. The network's structure and the possibilities of integrating technologies for determination of quasigeoidal deviation parameters are discussed. The integrating model for adjustment of 1D heterogeneous (leveling and GPS) height data with evaluation of the basic quasigeoid and the national/regional vertical datum is proposed.